2017
DOI: 10.1016/j.jsha.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria is a late event in patients with hypertension: Do we need a lower threshold?

Abstract: Many vascular changes, in the form of increased IMT, reduced vasodilator capacity, and increased arterial stiffness, preceded MA and any change in LV geometry. The results presented here strengthen the usefulness of adopting a lower cut-off to define MA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…To date, many studies have reported UACR cut-off values for diseases that are associated with diabetic diabetes, e.g., MA cut-offs of 19.25 mg/g Cr [19] for hypertension; 10.7 mg/g Cr [20], 15.6 mg/g Cr [21], 10.7 mg/g Cr [22], and 10.0 mg/g Cr [23] for diabetic retinopathy (DR); and 4.8 mg/g Cr [6] for metabolic syndrome. However, only four studies that investigated the cut-off values for type 2 diabetes [15], CKD [16], and DN [17,18] have been conducted.…”
Section: Uacr Cut-off Values For Diseases Associated With Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many studies have reported UACR cut-off values for diseases that are associated with diabetic diabetes, e.g., MA cut-offs of 19.25 mg/g Cr [19] for hypertension; 10.7 mg/g Cr [20], 15.6 mg/g Cr [21], 10.7 mg/g Cr [22], and 10.0 mg/g Cr [23] for diabetic retinopathy (DR); and 4.8 mg/g Cr [6] for metabolic syndrome. However, only four studies that investigated the cut-off values for type 2 diabetes [15], CKD [16], and DN [17,18] have been conducted.…”
Section: Uacr Cut-off Values For Diseases Associated With Diabetesmentioning
confidence: 99%
“…The confounding factor of MA has a ten-times wider range for definitions, e.g., UACR 30-300 mg/g Cr, and thus can allow the detection of various diseases associated with diabetes, because it was designed for multi-purpose use. To find the cut-offs for various diseases associated with diabetes, previous studies [13,15,16,[18][19][20][21][22] analyzed AUC-ROCs and used multivariate logistic regression analysis. However, continuous Re-RX can detect the UACR cut-off values for an indication of early DKD and various diseases that are associated with diabetes, without prior knowledge such as distributions/or assumptions of medical datasets.…”
Section: Significance and Clinical Relevance Of This Studymentioning
confidence: 99%
“…Urinary albumin level is a risk factor for CKD or CKD progression ( 52 , 53 ). However, in recent years, many studies have suggested that urinary albumin excretion below the defined microalbuminuria range (i.e., in the normal-to-mildly increased albumin range) is an independent risk factor for renal disease ( 54 , 55 ), and some studies have proposed the lowering of albuminuria levels that require intervention from 30 mg/24 h to 8–10 mg/24 h ( 56 , 57 ). These studies have led to an increasing demand for rapid and easy-to-use screening tests to detect low albumin levels in the general population ( 35 ).…”
Section: Auxiliary Examination Of Ckd Patients With Nanoparticlesmentioning
confidence: 99%
“…Progressive renal decline could be initiated at even 10% NA, 30% MA and 50% proteinuric states in DM patients [7]. Other vascular complications such as diabetic retinopathy and cardiovascular diseases may occur in diabetic patients in a normal to mildly increased albuminuric state; thus, recent studies have suggested a revised threshold for MA [8,9].…”
Section: Introductionmentioning
confidence: 99%